Establishment of a New Ovarian Cancer Cell Line CA5171. (June 2015) - Chiang, Ying-Cheng; Cheng, Wen-Fang; Chang, Ming-Cheng; Lu, Tzu-Pin; Kuo, Kuan-Ting; Lin, Hsiu-Ping; Hsieh, Chang-Yao; Chen, Chi-An
A new cell line, CA5171, derived from a chemotherapy-naive, high-grade undifferentiated ovarian carcinoma was established and characterized. The CA5171 cells presented with cobblestone morphology and a doubling time of 24 hours. Gene mutation analysis showed that the cells belonged to the type II ovarian cancer pathway with mutations of PIK3CA, PTEN, and TP53. Single-nucleotide polymorphism array analysis showed no homozygous gene deletion; however, several loci of gene copy number gains were noted in chromosome 1, 2, 5, 9, 10, 12, 15, 16, 20, and X. The in vitro and in vivo experiments showed that the cells were sensitive to paclitaxel and doxorubicin, but resistant to cisplatin. The cells also presented epithelial–mesenchymal transition properties that may have been related to their invasion and migration potential. The CA5171 cells show the potential as a new cell line for studies on epithelial ovarian carcinoma.